PENGARUH LATIHAN DOBLE LEG SPEED HOP TERHADAP DAYA LEDAK OTOT TUNGKAI PADA ATLET PENCAK SILAT LANGKAH HARIMAU RUMBAI PEKANBARU - Eko Hendrawan; Slamet Slamet; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Based on observations, researchers in the field observing both the training session and the competition in the athletes' Step Harimau martial arts are still lacking. One of them is like a leg muscle when kicking. So that when the kick is not optimal. This thing is not done well can be ignored by opponents. Based on the above problems, to increase the explosive power of the leg muscles, intensive and programmed training needs to be held. The purpose of this study was to determine the effect of double leg speed hop training on leg muscle explosive power in the Step Hari Pencak Silat athlete. The population in this study was the Putra Langkah Harimau pencak silat team who participated in the active training in the pencak silat branch, consisting of 10 sons. this study the sampling technique was carried out by means of total sampling, where the sample was a male team of 10 people sampled. The instrument in this research is vertical jump. Each group was taken from two measurements, namely in the pre-test before treatment and post-test after treatment was given. This aims to obtain research data that will be processed to test the hypothesis. Based on the data analysis and discussion, it can be concluded that there is an effect of the practice of Double leg speed hop on leg muscle explosive power. The Step Tiger pencak silat athlete is proven by the results of tcount 3.177> t table 1.833 at α = 0.05. This proves that by doing the Double leg speed hop exercise, the explosive power of the leg muscles can produce better results.Key Words; Double Leg Speed Hop, Leg Muscle Explosive Power